Influence of different nutrient sources on growth, yield and nutritive value of fodder maize - Safi, Mohibullah; Bishist, Rohit; Dr Bhardwaj,; Cl Thakur,; Prakash, Prem; Gautam, Krishan Lal; Dogra, Rushal; Sharma, Harish; Kishore , Kamal; Kengoo, Ngahanyui (Bangladesh Journal of Botany, 2024)
A study was carried out to assess the effects of two types of organic manure i.e., FYM (20 t ha-1) and Jeevamrut (500 L ha-1) and inorganic fertilizer (60 N kg ha-1) on growth and yield performance of fodder maize. The application of recommended dose of fertilizer (RDF) (T3) significantly increased fodder maize plant height (170.03 cm), number of leaves per plant (12.40), leaf length (92.76 cm), leaf width (8.00 cm), stem girth (5.93 cm), green fodder yield (29.20 t ha-1) and dry matter yield (7.99 t ha-1). The nutritional parameters were also better on the application of RDF with CP 8.40, EE 0.98, TA 8.08, AIA 1.09, NFE 52.38, DM 27.37, CF 30.15, NDF 55.37, and ADF 35.29 %. The application of RDF resulted in better plant growth parameters as compared to FYM and Jeevamrut. Bangladesh J. Bot. 53(4): 923-929, 2024 (December)